PELINDUNGAN EKSPRESI BUDAYA TRADISIONAL OLEH PEMERINTAH DAERAH KOTA SURAKARTA BERDASARKAN UNDANG UNDANG NOMOR 28 TAHUN 2014 TENTANG HAK CIPTA - Kumala, Revitta Ratna (Res Publica: Jurnal Hukum Kebijakan Publik, 2025)
This research aims to determine the implementation of protection of traditional cultural expressions by the Surakarta City Regional Government based on Law Number 28 Year of 2014 concerning on Copyright, as well as to determine the factors that can support and hinder the successful implementation of protection of traditional cultural expressions by the Surakarta City regional government. This research is empirical juridical legal research with a qualitative approach. The types and sources of legal research data used in this research are primary legal materials and secondary legal materials. Data collection carried out was interviews and literature study. The data analysis technique used is qualitative, comprehensive and complete.The result obtained from this study are that the implementation of protection by the Surakarta City regional government is not in accordance with Law Number 28 of 2014 concerning Copyright as evidenced as the implementation of Surakarta City Regional Regulation Number 4 of 2018 concerning the Promotion of Intangible Cultural Heritage by the regional government is not optimal. It was also found that the process of implementing the protection of traditional cultural expressions in the city of Surakarta was influenced by several important factors, including supporting factors and inhibiting factors for this implementation.